Neutronic Performances of 100 MWe MSR with Weapon Grade Plutonium Fuel. Issue 1 (June 2021) - Wulandari, C; Waris, A; Permana, S; Pramuditya, S
Abstract: An advanced nuclear reactor Generation IV, called Molten Salt Reactor (MSR), has been developed with Thorium utilization for a sustainable energy system. In this paper, the study is focused in the neutronic calculation of 250 MWt/100 MWe MSR with Thorium-Plutonium (Th-Pu) fuel salt for 5 years time operation. Fuel salt is composed of a eutectic FLiBe, Th, and Pu, as a coolant, fertile, and fissile nuclide, respectively. Pu loaded is a weapon-grade which consist of 238 Pu, 239 Pu, 240 Pu, 241 Pu, 242 Pu, and 241 Am. The reactor is operated in the thermal energy range and moderated by the graphite. The reactor design is calculated in neutronic terms with program code CITATION in SRAC 2006 with JENDL 4.0 as a nuclear data library. The result shows some neutronic parameter changes with increasing Plutonium loaded and the reactor criticality is obtained for 5 years by minimal loaded of PuF4 of 2.41%mol. The utilization of Plutonium is described as a capability of MSR in burning a high-level waste of nuclear and radioactive isotopes. This system can be dedicated to future cleaning energy production in a nuclear reactor.